Analisis Etika dalam Transaksi E-Commerce pada Platform Shopee di Indonesia - Dinda Naurah Aidil Nafilah; Evy Nurmiati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines the implementation of Islamic business ethics in e-commerce transactions, with a specific focus on the Shopee platform. The research is motivated by the increasing growth of digital commerce accompanied by various ethical issues such as product misrepresentation, lack of transparency, and weak accountability of sellers. The objective of this study is to analyze how ethical principles, including honesty, fairness, and responsibility, are applied in online transactions. This research employs a qualitative approach using a systematic literature review method by analyzing 20 relevant scholarly articles published between 2020 and 2026. The findings reveal that although the platform provides adequate transactional systems, ethical violations are still prevalent, primarily due to information asymmetry between sellers and consumers. Trust emerges as the most influential factor in purchasing decisions, while perceived risk and security play supporting roles in shaping consumer behavior. Additionally, economic incentives such as promotions often override ethical considerations in influencing consumer decisions. The study implies that strengthening ethical enforcement, enhancing platform supervision, and improving consumer digital literacy are essential to ensure a sustainable and trustworthy e-commerce ecosystem.